Resid?ncia Multiprofissional em Sa?de da Fam?lia e as repercuss?es no processo de trabalho na aten??o prim?ria ? sa?de - Gomes, Ana Elisa dos Santos (2024)
The inclusion of residents of the Multidisciplinary Residency in Family Health in primary health care requires attention, especially due to the work of local workers in health units in the territories. Therefore, integration between these workers and residents is essential to ensure the adequate training of students and the continuity of quality work in the teams. Therefore, the objective of this research was to analyze the work process in primary health care after entering the residence in a municipality in the interior of Bahia. To this end, a qualitative approach was adopted, in which eleven workers participated, with data collection carried out through semi-structured interviews and field diary records, both of which took place between the months of July and September 2023. The analysis of the collected material was conducted using Thematic Content Analysis. From this material, five categories of analysis emerged: 1) characterization of workers: mapping the stars in the constellation of work; 2) unveiling the work process: dynamics of the stars; 3) stellar collaboration: the stars, residents, and their alignments in the work process; 4) stars and residents: analyzing practices among professionals 5) revealing synergies: emerging elements in the universe of constellations. The research revealed that poor infrastructure, such as lack of water and inadequate air conditioning, negatively impacts the quality of care. The lack of transport limits home care, which is crucial for distant areas. Institutional meetings and planning are essential, but face challenges due to disagreements and conflicts. Team meetings, together with residents, are essential to align activities. This collaboration enriches the training of residents and the performance of workers, resulting in a more efficient and coordinated service. The interaction between residents and workers strengthens health activities, promoting comprehensiveness and quality in care. However, there are challenges such as the lack of participatory planning and the overload of workers, indicating the need for greater involvement in the planning and execution stages of actions. Interdisciplinarity and matrix support are fundamental for effective and comprehensive care. Collaboration between residents and health workers in the units revealed new perspectives of holistic and multidisciplinary care, encouraging creativity and improvements in performance. This exchange resulted in shared learning, recognition of the importance of health workers and development of skills, enriching practice and benefiting users of health services. The results of this research aim to promote reflection on the new aspects of the workers' work process after entering the residency, while at the same time seeking to strengthen integration between everyone involved. Furthermore, the findings highlight the need to establish Continuing Health Education as an institutional arrangement in services, along with incentives to improve working conditions for both residents and health service workers.